Pembuatan Animasi Motion Graphic dalam Pembelajaran Akuntansi Bagan Akun Standar untuk Jurusan Akuntansi Politeknik Negeri Sriwijaya - Alisa Rosalina; Isnainy Azro; Alan Novi Tompunu (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
In the midst of this COVID-19 pandemic season, learning activities are carried out online and a lecturer is required to be more creative in terms of delivering material and information to students. One solution is learning animation videos. Therefore, the purpose of the research on "Creating Motion Graphic Animation in Accounting Learning Standard Chart of Accounts for the Sriwijaya State Polytechnic Accounting Department" is to find out how effective this standard account chart learning animation video can convey standard account chart material to students in the online learning process. In this learning animation video, the material to be delivered is packaged with a fictional story played by 2D characters so that it becomes more interesting to know. Keywords: learning animation videos, accounting, standard chart of accounts